Motivation for Consumers to Choose Shared Economy Accommodations within the Tourism Industry - Agrawal, Diksha (2016)
The study aims at examining the motivations for consumers to choose shared economy accommodation in the tourism industry. Since the shared accommodation sector did emerge recently, only limited research has so far examined in this sector. However, I decided to do research in this sector to discover some new motivations that drive customers to choose this sector. Exploratory research was conducted and involved gathering qualitative data using interviews. In particular, few researchers have explored the important question of why so many tourists use the service. Consequently, the purpose of this study was to investigate the reasons tourists choose to stay in Airbnb accommodations. The study focused on exploring the motivations that attract tourists to shared accommodations. The sample considered in the study consisted of 17 interviewees who have used shared accommodation while their travel plans. The questions concerned the consumer decision making process regarding the private shared accommodations in the travel industry. Thematic analysis helped to code the responses obtained using cluster method and hence enabled the major themes arising from the responses obtained. In particular, the research found different motivations which were examined to highlight the importance of practical considerations. The motivational characteristics are discussed in detail to provide direct marketing implications for shared accommodation and hosts. The two main motivations factors found in the study are low cost and authenticity along with other practical and experiential attributes. The performance expectations of private shared accommodations are shown to indicate some consistency with the concept of disruptive innovation, while also demonstrating the value in using a demand-side perspective to assess the concept. This study additionally more broadly demonstrates that shared accommodations presents a real threat to the traditional accommodation sector. Areas for potential future research also are explained.